2001
DOI: 10.1677/joe.0.1700147
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of beta2-adrenoceptor function in non-pregnant rat myometrium is modulated by sex steroids

Abstract: The effects of in vivo treatment with estrogen and progesterone on isoproterenol-induced uterine relaxation and 2 -adrenoceptor ( 2 AR) mRNA production in nonpregnant rat myometrium were investigated. Whether homologous myometrial desensitization of 2 AR function was dependent on or modulated by the two steroids was also examined.Estrogen treatment alone or in combination with progesterone reduced maximal relaxation (E max ) of isolated uterine strips subsequently challenged with isoproterenol whereas progeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…These effects could be confirmed by a characteristic loss of tracheal tone (for about 30 min) to continued occupancy of ␤ 2 -adrenoceptors due to subsequent agonist stimulation (Katsunuma et al, 2000). The ␤-adrenergic desensitization has also been observed in vitro rat myometrium (Johansson and Andersson, 1981;Engstrom et al, 2001). In conclusion, based on our results, we suggest that Viburnum prunifolium is able to relax isolated rabbit jejunum and guinea-pig trachea through an interaction with the ␤-adrenergic system.…”
Section: Discussionsupporting
confidence: 78%
“…These effects could be confirmed by a characteristic loss of tracheal tone (for about 30 min) to continued occupancy of ␤ 2 -adrenoceptors due to subsequent agonist stimulation (Katsunuma et al, 2000). The ␤-adrenergic desensitization has also been observed in vitro rat myometrium (Johansson and Andersson, 1981;Engstrom et al, 2001). In conclusion, based on our results, we suggest that Viburnum prunifolium is able to relax isolated rabbit jejunum and guinea-pig trachea through an interaction with the ␤-adrenergic system.…”
Section: Discussionsupporting
confidence: 78%
“…This effect of estrogen was not altered by concomitant progesterone treatment. It was concluded that the process of b 2 -AR function desensitization was independent of the sex steroids (Engstrom et al 2001). Our experiment revealed increased levels of b 2 -AR mRNA and b 2 -AR on days 20 and 22, respectively.…”
Section: Discussionsupporting
confidence: 46%
“…Earlier studies suggested that the presence or absence of progesterone can alter the effect of b 2 -AR agonists on the pregnant myometrium (Dowell et al 1994, Engstrom et al 2001. On the basis of the sex hormone levels at the end of pregnancy, the pregnant animals were treated with progesterone for 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen has been shown to suppress the responsiveness to ␤-AR stimulation in the hypothalamus of rats (Ungar et al, 1993;Ansonoff and Etgen, 2001) and myometrium of rats (Ruzycky and DeLoia, 1997;Engstrom et al, 2001). In the hypothalamus, estrogen uncouples the receptor and the G protein (Ungar et al, 1993;Ansonoff and Etgen, 2001), whereas in the myometrium, estrogen increases the ␤-ARinactivating kinase (Ruzycky and DeLoia, 1997).…”
Section: Discussionmentioning
confidence: 99%